Confronting E-Government Adoption in Indonesian Local Government - Martitah, Martitah; Arifin, Saru; Sumarto, Slamet; Widiyanto, Widiyanto (JILS (Journal of Indonesian Legal Studies), 2021)
Indonesia passed an e-government law in 2018, ushering the country's society into the information age across a range of sectors, including social, economic, communication, transportation, literacy, and public services. This transformation has benefited enormously from the facilitation of information technology in terms of productivity, comfort, compassion, and time elapsed. Local governments in Indonesia, on the other hand, are slowing the adoption of e-government, which has progressed to the second stage of implementation, which is the introduction or integration of cross-sectoral systems. This article claims that local governments face challenges in this second stage as a result of departmental egos that make it difficult to unite around shared objectives. The whole government approach is suggested in this paper as a concrete policy strategy for eradicating sectoral egos within local government departments. It places a premium on collaboration in order to accomplish the government's vision and objectives.